Pemberian Jenis Nutrisi dan Konsentrasi Nutrisi terhadap Pertumbuhan Sawi Pakcoy (Brassica Rapa Subssp. Chinensis) Secara Hidroponik Rakit Apung - Harahap, Evi Julianita; Chairudin, Chairudin (Savana Cendana, 2024)
The research was conducted at the Green House of the Faculty of Agriculture, Teuku Umar University, Meulaboh, West Aceh, starting from March to June 2021. The research used a factorial Completely Randomized Design (CRD) with 3 replications. The factors studied included the type of nutrients and the concentration of nutrients. The Type of Nutrient Factor (J) consisting of 3 levels, namely: J1 = AB mix nutrients, J2 = Hydro J nutrients, and J3 = Goodplant nutrients and the Nutrient Concentration Factor (K) consisting of 3 levels, namely: K1 = 600 ppm, K2 = 800 ppm, and K3 = 1000 ppm. The results showed that the type of nutrients had a significant effect on plant height, number of leaves, and leaf length on the growth of pak choi mustard greens. The best type of nutrient treatment was treatment J3 (Goodplant nutrients) on the growth of pak choi mustard greens on the number of leaves parameter. Nutrient concentration had a significant effect on plant height, number of leaves, and leaf length on the growth of pak choi mustard greens. The best nutrient concentration was found in the K3 treatment (1000 ppm) on the growth of pak choi mustard greens on the parameters of leaf height, number of leaves, and leaf length. The interaction of nutrient types and nutrient concentrations had a significant effect on plant height, number of leaves, and leaf length on the growth of pak choi mustard greens. The best interaction of nutrient types and nutrient concentrations was found in the J3K3 treatment (Goodplant nutrients and 1000 ppm) on the parameter of plant height at 28 HST and the J2K3 treatment (Hydro J nutrients and 1000 ppm) on the parameter of number of leaves at 14 HST on the growth of pak choi mustard greens.